Feasibility and potential value of a local governmental frail check-up program for the risk assessment of long-term care in apparently healthy older citizens: a prospective study - Yoji Nagai; Yasumasa Kakei; Tatsuo Kagimura; Shinsuke Kojima; Hisatomo Kowa; Tohmi Osaki; Ryoma Kayano; Yasuji Yamamoto (BMC Health Services Research)
Abstract Background Earlier identification of individuals at risk of needing long-term care can increase the opportunities for preventive/therapeutic interventions, leading to a reduced social burden. Methods We examined the feasibility and potential value of a frailty check-up program implemented by the local government for risk assessment of long-term care needs in 1,528 apparently healthy older (aged 64/65 years) citizens in Kobe, Japan, between August 2017 and March 2018. The program comprised a questionnaire on general frailty (Comprehensive score) and evaluation of other frailty-related measures, cognitive function-related activities of daily living (Cognitive Function Instrument), and health-related quality of life (EQ-5D-5L). In March 2020, these measures were merged with data on long-term care or support certification, where the latter represented a condition requiring care for a certain period preceding long-term care needs. Results Overall, 15 citizens were certified as having long-term care needs and 38 as having long-term care or support needs. Using receiver operating characteristic curve analysis, certain measures, including the Comprehensive score and EQ-5D-5L, significantly predicted the incidence of long-term care or support needs. Conclusions The frailty checkup program conducted by the local government may be feasible and valuable for risk assessment of long-term care needs in apparently healthy older citizens.